Contribuições do aconselhamento psicológico para a prática da direção espiritual - Pisaneschi, Vandro (2009)
The objective of this dissertation is to research possible contributions of psychological counseling under Person-Centered Approach to the practice of spiritual direction, according to the Catholic religion perspective, in the light of interdisciplinary dialogue. In order to achieve this objective, introduce yourself at first psychological counseling as a help relationship through which the counselor tries to help the advised person to find his own way and lead a good full life. Secondly, present spiritual direction as a spiritual help relationship in the light of the faith in Jesus Christ, between spiritual director and directee in which the first helps the second to observe God´s signs through his own life experiences in order to improve his relationship with himself, with others and with God himself. After presenting two help relationships, established a dialogue between both, showing their similarities, differences and implications for the practice of spiritual direction. To conclude, present appropriations of concepts and attitudes of the psychological counseling in the practice of spiritual direction